Çocukluk çağı üriner sistem taş hastalığınınetiyolojik değerlendirmesi ve izlem sonuçları - Saygın, Mesut (My University, 2022)
Üriner sistem taş hastalığı (ÜSTH), çocuklarda sıklığı giderek artan önemli bir klinik problemdir. Klasik semptom ve bulgular çocuklarda yetişkinlere kıyasla daha belirsiz olabilir. Bu çalışmanın amacı ÜSTH tanısı ile izlenen çocuk hastaların demografik ve etiyolojik özelliklerinin, biyokimyasal parametrelerinin taş oluşumuna etkilerinin gösterilmesi, tedavide uygulanan medikal ve girişimsel yöntemlerinin etkinliğinin ve izlem sonuçlarının değerlendirilmesidir. İstanbul Medipol Üniversitesi Tıp Fakültesi, Çocuk Nefroloji Bilim Dalı'nda 26.10.2018 ile 10.10.2021 tarihleri arasında ÜSTH tanısıyla takip edilen 176 hasta retrospektif olarak değerlendirildi. Hastaların cinsiyeti, yakınması, tanı yaşı, aile öyküsü, başvuru anında Fizik bakı bulguları, spot idrar analizi, biyokimyasal parametreleri, US bulguları, üriner sistem anomalileri, taş analizi, uygulanan medikal ve cerrahi tedaviler ve izlem sonundaki durumu değerlendirildi.

Urinary system stone disease is an important clinical problem with an increasing frequency in children. Classical symptoms and signs may be more uncertain in children than in adults. The aim of this study is to show the effects of demographic and etiological features and biochemical parameters on stone formation in pediatric patients followed up with the diagnosis of Urinary system stone disease, to evaluate the effectiveness of medical and interventional methods used in treatment and the results of follow-up. 176 patients who were followed up with the diagnosis of Urinary system stone disease between 26.10.2018 and 10.10.2021 in Istanbul Medipol University Faculty of Medicine, Department of Pediatric Nephrology were evaluated retrospectively. The patients' gender, complaints, age at diagnosis, family history, physical examination findings at the time of admission, spot urine analysis, biochemical parameters, US findings, urinary system anomalies, stone analysis, medical and surgical treatments applied, and status at the end of the follow-up were evaluated.
Etiological evaluation and follow-UP results ofchildhood urinary tract stone disease
Keywords: Çocuk; Üriner Sistem Taşı; Nefrolitiazis; Ürolitiazis; Böbrek Taşı; Child; Kidney Stone; Nephrolithiasis; Urinary System Stone; Urolithiasis